Influência da espiritualidade na experiência de abstinência do indivíduo com transtorno por uso de substância (TUS) - Soares, Valterdes Fábio Pessoa (2019)
The present study highlights that chemical dependence is a multifaceted collective health problem, and there is a need to modify the conditions that cause exclusion and break out in the drug abuser intense psychological distress. In this context, this study identified and analyzed how spirituality was involved in the withdrawal experience of individuals with substance-related disorders (SRD). For this, we examined the spiritual factors in the abstinence period of a group of subjects, who narrated social practices and knowledge involved in their abstinence period. The research was carried out at Elo de Vida Day Hospital, a branch of Professor Frota Pinto Mental Health Hospital. A qualitative approach was used, according to Focal Group methodology, with a multi-method proposal, through which was implemented a listening mode capable of focusing on life course and experiential contexts mentioned by subjects undergoing the problematic of SRD. Based on the mentioned methodology, it was observed that drug use relapses were related to the absence of the subject self-responsibility in avoiding abusive use of substances, in a lack of authority over their own acts and choices. It was concluded that the value of spirituality during abstinence process focuses, above all, on “taking care of others”, which can again draw the subject to his commitment to change, upon his reflections on bonds and articulating of dimensions involved in widely understanding the relationship with oneself, the others and the social environment. It was found, therefore, that the development of one dimension (that of spirituality) may be able to propel the unfolding of other dimensions (affective and social, for example), which are fulcrum points for maintaining abstinence, through what we have named and described as a progression by links. It has been found that extrinsic spirituality acts most visibly in the crisis, while a deepening of self-knowledge and, therefore, intrinsic spirituality acts in the production of more lasting effects, since it involves the production of spiritual senses on the human being, according to the subjects experiences, which emphasizes autonomy and reflexivity in the operationalization of choices. Through the articulation between the theory of Paul MacLean(1990) on the Triune Brain and André Luiz(2006) thoughts, it is concluded the worth of proposing a work with several instances of the mind, situated in the Spirit, and in correspondence with the health subject, which must be taken in a multidimensional way, according to this theoretical understanding.